Quality of Blue swimming crab Portunus pelagicus Larvae from Domesticated Broodstock - Trijuno, Dody Dharmawan; Fujaya, Yushinta; Agviranti, Agviranti; Marhama, Syamsurya (Indonesian Aquaculture Society (MAI), 2015)
Blue swimming crab (Portunus pelagicus) is the important world fishery resource, but the crab larval rearing faces high mortality problem. The aim of the research was to compare survival and growth rate of larvae resulted from wild and domesticated broodstock blue swimming crab. Domesticated and wild broodstock were used to produce larvae. Domesticated broodstock was selected from repeated reared crab until third generation. Selection of the broodstock mainly based on the survival and growth rate. The wild broodstock was collected from Makassar Strait Sea. Larvae from the two sources of broodstock were reared in the conical tanks with density of 50 zoeas per liter. After reaching megalopa phase, then, the larvae were transfered into concrete tank completed with shelter and it were reared until crab phase. Crab phase was reared for 18 days, then these seed were released into the brackishwater pond for further domestication step. Larva from zoea to crab were fed with rotifer, artemia, fresh small shrimp and diet. The result showed that domesticated broodstock produced higher survival rate (P<0.05) larvae, faster larval stage changes (P<0.01) and uniform larval growth compared to the larvae from wild broodstock. It is clearly shown, the use of domesticated broodstock of blue swimming crab produced better larva quality and quantity than the wild broodstoock crab.Keywords : blue swimming crab, larvae, domestication, broodstock selection, faster growth